KONSTRUKSI PENDIDIKAN KARAKTER DALAM AL-QURAN : ANALISIS TEMATIK SURAT LUQMAN DAN IMPLEMENTASINYA DI ERA DIGITAL - Apipah, Nurul; Suhendar, Otong (As-Sulthan Journal of Education, 2025)
This study examines character education in the Qur’an through a thematic analysis of Surah Luqman and its implementation in the context of the digital era. The scope of the study covers the key values found in Surah Luqman, including monotheism as the foundation of faith, filial piety, gratitude, responsibility for actions, worship and patience, and social ethics. The aim of this research is to explore the relevance of these values in addressing the challenges of character education in the digital age, marked by the dominance of technology and social media. The method employed is qualitative with a library research approach, utilizing literature on Qur’anic exegesis, Islamic education studies, and recent findings on character education and digital ethics. The findings indicate that the character values in Surah Luqman can be implemented through contextual strategies such as digital learning platforms, technology-based collaborative projects, social media integration for positive content, strengthening digital literacy and ethics, and fostering synergy between teachers and parents. The study concludes that Qur’an-based character education remains relevant and adaptive in responding to digital globalization, fostering a generation that is not only academically competent but also morally upright and digitally wise.